Diabetic macroangiopathy and self-monitoring of glucose - OS Fedorova (Медицинский совет, 2014)
Diabetic macroangiopathy is a general term for atherosclerotic vascular diseases of large- and medium-caliber arteries in diabetes mellitus (DM). Macrovascular complications of diabetes leading to cardiovascular diseases (CVD) are the major cause of death in patients with diabetes. CVD are less dependent on hyperglycemia or the rate of glucose lowering than microvascular complications. At the same time, there are big research works confirming this relationship. Diabetic macroangiopathies include coronary heart disease (CHD), cerebrovascular disease (CVD), chronic obliterating peripheral arterial diseases [1].